A new diterpenoide from Isodon lophanthoides var. gerardianus. (1st January 2013) - Yang, Libin; Liu, Shaojing; Wang, Honglun; Suo, Yourui
A new diterpenoid, 11, 12-dihydroxyabieta-7-oxo-8, 11, 13-trien-15-ol, along with two known diterpenoids were isolated from the roots of Isodon lophanthoides var. gerardianus. The structures of the three compounds were elucidated by spectroscopic methods and literatures.